Gene expression profile in response to Xanthomonas axonopodis pv. manihotis infection in cassava using a cDNA microarray - López, C.E.; Soto Suárez, M.; Restrepo, S.; Piegu, B; Cooke, R.G.; Delseny, M; Tohme, Joseph M.; Verdier, Valerie M. (Springer, 2005)
A cassava cDNA microarray based on a large cassava EST database was constructed and used to study the incompatible interaction between cassava and Xanthomonas axonopodis pv. manihotis (Xam) strain CIO151. For microarray construction, 5700 clones from the cassava unigene set were amplified by polymerase chain reaction (PCR) and printed on glass slides. Microarray hybridization was performed using cDNA from cassava plants (resistant variety MBra685) collected at 12, 24, 48 h and 7 and 15 days post-infection as treatment and cDNA from mock-inoculated plants as control. A total of 199 genes were found to be differentially expressed (126 up-regulated and 73 down-regulated). A greater proportion of differentially-expressed genes was observed at 7 days after inoculation. Expression profiling and cluster analyses indicate that, in response to inoculation with Xam, cassava induces dozens of genes, including principally those involved in oxidative burst, protein degradation and pathogenesis-related (PR) genes. In contrast, genes encoding proteins that are involved in photosynthesis and metabolism were down regulated. In addition, various other genes encoding proteins with unknown function or showing no similarity to other proteins were also induced. Quantitative real time PCR experiments confirmed the reliability of our microarray data. In addition we showed that some genes are induced more rapidly in the resistant than in the susceptible cultivar.